2021
DOI: 10.1051/mbcb/2020063
|View full text |Cite
|
Sign up to set email alerts
|

Decompression: a first-intention treatment for “large” non-syndromic odontogenic keratocysts

Abstract: Though odontogenic keratocysts (OKCs) are benign lesions, they have a high recurrence rate. Because of their aggressive behavior, they have been classified as tumors by the WHO until 2017. Main differential diagnoses are amelobastoma and dentigerous cyst. Anatomopathological examination can reach a final diagnosis. Several treatments have been proposed: curettage, resection, enucleation (alone or together with peripheral ostectomy) and decompression. Decompression aims to decrease the volume of the lesion of “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…It was reported that the recurrent rate of OKC treated by decompression followed by enucleation be significantly lower than enucleation alone." (37,55) Another essential things decreasing OKCs recurrence rate are removal of covering oral epithelium, particularly when the cyst is biopsied. Several types of research demonstrate that about whole recurrent OKCs have microcysts in the mucosa covering cortical perforation sites.…”
Section: Microscopical Findingsmentioning
confidence: 99%
“…It was reported that the recurrent rate of OKC treated by decompression followed by enucleation be significantly lower than enucleation alone." (37,55) Another essential things decreasing OKCs recurrence rate are removal of covering oral epithelium, particularly when the cyst is biopsied. Several types of research demonstrate that about whole recurrent OKCs have microcysts in the mucosa covering cortical perforation sites.…”
Section: Microscopical Findingsmentioning
confidence: 99%
“…Thus, the treatment goal is to first reduce intracystic pressure using decompression techniques, such as decompression with a drain or marsupialization, which should be considered to prevent potential damage. 5 , 6 , 7 , 8 …”
Section: Introductionmentioning
confidence: 99%